Conciencia ambiental y su relación con el comportamiento ecológico en la Unidad Educativa Particular Católica “Pedro Schumacher” del cantón Tosagua - Loor Loor, Tatiana Lilibeth (2021)
The aim of the research was to relate environmental awareness to ecological behaviour at the EU "Pedro Schumacher". The learning-by-doing method and the techniques of questionnaires, semi-structured interviews and participatory observation were used to measure the variables under study in three study phases. The first phase diagnosed the level of environmental awareness and ecological behaviour of the students; the second phase was based on the implementation of an intervention programme for the development of environmental awareness; and the third phase compared environmental awareness and ecological behaviour. It was found that, initially, environmental awareness is mainly strengthened in the knowledge about "plant and animal rights" (64.9%), and for environmental behaviour it was "energy optimisation". The intervention programme significantly strengthened environmental awareness and ecological behaviour. However, the Chi-square test revealed that, out of 12 aspects analysed on the relationship between environmental awareness and environmental behaviour, in 9 there was significance (p >0.05) and in 3 there was no high significance (p <0.01). It is concluded that there is a high relationship between environmental awareness and ecological behaviour.